Sustaining faith [large type] - Oke, Janette, 1935-; Logan, Laurel Oke (Oke, Janette, 1935- When hope calls, 2021)
"So much has been accomplished. Lillian Walsh has stepped out courageously beyond what she'd ever dreamed of being able to achieve. She and her newly rediscovered sister, Grace, have settled three children from England into new Canadian homes and are prepared to place two more just after the New Year, when it happens--another painful disruption. A white lie the sisters used to protect some orphans has resulted in an official complaint and a letter revoking the sisters' permission to manage their little children's home. And unexpectedly, Walter, the young man who has won Lillian's heart, departs for a job in the oil industry without leaving any hope for their future, making her confused and lonely.With more children on their way from England needing caring homes, Lillian and Grace must use every ounce of gumption to keep their mission alive. But when startling information about the past surfaces and a new arrival comes via suspicious circumstances, they'll have to decide what is worth fighting for and what is better left in God's hands"--Provided by publisher.